2006
DOI: 10.1371/journal.pgen.0020172
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and Tissue Specificity of Expression Quantitative Trait Loci

Abstract: Variation in gene expression is heritable and has been mapped to the genome in humans and model organisms as expression quantitative trait loci (eQTLs). We applied integrated genome-wide expression profiling and linkage analysis to the regulation of gene expression in fat, kidney, adrenal, and heart tissues using the BXH/HXB panel of rat recombinant inbred strains. Here, we report the influence of heritability and allelic effect of the quantitative trait locus on detection of cis- and trans-acting eQTLs and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
185
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(201 citation statements)
references
References 39 publications
(59 reference statements)
16
185
0
Order By: Relevance
“…Local eQTL had higher mapping scores than distant loci (Wilcoxon rank test, P = 1.7e-07). This is consistent with previous work showing that while both local and distant eQTL exist, local eQTL typically have stronger effects (Petretto et al 2006a;Mackay et al 2009;Van Nas et al 2010). A targeted search for local eQTL where we tested only the marker situated closest to a given gene revealed local eQTL at 12% of the genes tested, for a total of 1161 local eQTL (Table S5).…”
Section: Genomic Architecture Of Mrna Expressionsupporting
confidence: 89%
“…Local eQTL had higher mapping scores than distant loci (Wilcoxon rank test, P = 1.7e-07). This is consistent with previous work showing that while both local and distant eQTL exist, local eQTL typically have stronger effects (Petretto et al 2006a;Mackay et al 2009;Van Nas et al 2010). A targeted search for local eQTL where we tested only the marker situated closest to a given gene revealed local eQTL at 12% of the genes tested, for a total of 1161 local eQTL (Table S5).…”
Section: Genomic Architecture Of Mrna Expressionsupporting
confidence: 89%
“…The establishment of gene-to-gene relationship revealed the specific regulatory network affecting maize kernel development, although parts of which may be shared between tissues 24 . In the regulatory networks, 455 transcription factors (TFs) were found to regulate gene expression and 44 of these TFs were predicted to regulate the expression of other TFs (Supplementary Table S11).…”
Section: Articlementioning
confidence: 99%
“…These genes represent members of a regulatory network that might contribute to the flexibility of the organism in regards to expressing low-heritable traits in response to different stimuli. Moreover, it was shown that the expression level of the trans-regulated genes was less heritable than that of cis-regulated genes (Petretto et al, 2006). Overall, this implies that the expression of genes associated with traits that have low heritability, like drip loss or pH, is largely dependent on trans regulation and is low in heritability.…”
Section: S Ponsuksili Et Almentioning
confidence: 99%